1972
DOI: 10.1113/jphysiol.1972.sp010044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of hepatic nerve stimulation on arterial flow, distribution of arterial and portal flows and blood content in the livers of anaesthetized cats and dogs

Abstract: SUMMARY1. The responses to hepatic nerve stimulation were studied in cats and dogs anaesthetized with sodium pentobarbitone. In three series of experiments, hepatic arterial flow was recorded by an electromagnetic flowmeter, intrahepatic distributions of arterial and portal flows were studied by radioactive microspheres, and hepatic volume responses were measured by a plethysmographic method.2. In cats, nerve stimulation produced a frequency-dependent decrease in hepatic arterial flow which was not maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
3

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 35 publications
1
35
1
3
Order By: Relevance
“…This trend faded away as SAP rose further with more severe cerebral ischemia. In the present study, an average blood volume of 8.4 ml/100 g of tissue was mobilized from the liver by maximum cerebral ischemic pressor response in a normovolemic state, but this value was slightly lower than the results obtained in dogs by hepatic nerve stimulation (GREENWAY and OSHIRO, 1972). Slight expansion of the skeletal muscle vascular volume during the initial pressor response with a modest reduction of cerebral blood flow regardless of the volemic status in animals may be attributed to the following.…”
Section: Discussioncontrasting
confidence: 37%
“…This trend faded away as SAP rose further with more severe cerebral ischemia. In the present study, an average blood volume of 8.4 ml/100 g of tissue was mobilized from the liver by maximum cerebral ischemic pressor response in a normovolemic state, but this value was slightly lower than the results obtained in dogs by hepatic nerve stimulation (GREENWAY and OSHIRO, 1972). Slight expansion of the skeletal muscle vascular volume during the initial pressor response with a modest reduction of cerebral blood flow regardless of the volemic status in animals may be attributed to the following.…”
Section: Discussioncontrasting
confidence: 37%
“…Girbes et al [20] reported improved postoperative healing in high-risk patients who had pre-operative volume replacement. Greenwas et al [21] showed that volume replacement increases liver perfusion through both a decrease in hepatic vascular resistance and an increase in cardiac output. In our study, baseline cardiac output was similar in the two groups, while indocyanine green clearance was higher in the crystalloid group.…”
Section: Discussionmentioning
confidence: 99%
“…O fl uxo sanguíneo hepático em gatos é citado como em torno de 21mL kg -1 min -1 (GREENWAY & OSHIRO, 1972), assim, os valores de clearance do propofol encontrados estão iguais ou abaixo destes, o que pode indicar baixa extração hepática do fármaco. BESTER (2009), supôs que, devido a esta extração defi ciente, o débito cardíaco pouco infl uenciaria na depuração do propofol em felinos, pois a variação do fl uxo não seria signifi cativa.…”
Section: Resultsunclassified